The role of pharmacist in early phase clinical research - A. V. Vozzhaev; S. B. Fitilev; V. A. Yakushev; I. I. Shkrebneva (Izdatelstvo OKI, 2018)
This article discusses the role of pharmacist in early phase clinical trials. Authors emphasize that in Russian phase I units pharmacists are rarely involved in clinical research activities. Probably the lack of regulatory documentation in this field is one of the main reasons. The opposite situation occurs abroad where pharmacist is key member of investigational team. This problem is particularly relevant because number of phase I studies in Russia steadily increases over the last years. Based on their practical experience authors describe the range of pharmacist functions and responsibilities when working in early phase research. Qualification requirements and skills of such specialist are pointed out as well. Due to the fact that not only number of trials but also number of phase I units increases (including private departments) the value of pharmacist in clinical research will grow.